Bridging Sustainable Bank Performance through Fintech and Enacted Norms - Steph Subanidja; Fangky A. Sorongan; Mercurius B. Legowo (Ital Publication, 2023)
Since the launch of green banking, the Government Authority still needs to accommodate enacted norms and fintech in measuring sustainable bank performance. Empirically, this study aims to reveal the impact of variables and business drivers on sustainable bank performance. This research uses a quantitative approach through path analysis. By analysing 70 out of 78 bank managers or directors who are members of the National Banking Association as respondents, this study states that business drivers, fintech, and enacted norms encourage sustainable bank performance improvement. In addition, fintech and enacted norms are suitable as moderating and exogenous variables for sustainable bank performance, but the variables are not endogenous variables for business drivers. In addition, fintech and enacted norms can bridge the achievement of sustainable bank performance. The originality of this research is that enacted norms and fintech are the moderating variables in realising bank sustainability. The research suggests that enacted norms should be one of the new dimensions in measuring bank sustainability, and the existence of fintech could be an integral part of realising sustainable bank performance. Doi: 10.28991/ESJ-2023-07-06-017 Full Text: PDF